Investigating self-regulation in young adults who drug-drive. (10th March 2022) - McManus, Shaun Anthony; Watson-Brown, Natalie; Truelove, Verity
Abstract: Objective: Drug-driving among young adults is a growing concern. Methods other than enforcement are required to reduce engagement in such behavior. Research has identified satisfaction of individual's inherent psychological needs is predictive of positive behavioral outcomes sustainable in the long-term via the internalization of self-regulatory processes. Drug-driving behavior and self-regulation was explored through the lens of self-determination theory's needs-supportive model. Methods: An online cross-sectional survey of 304 participants (males = 78), aged 18-24 years ( M  = 20.61, SD  = 1.92) was conducted. Participants were recruited via convenience sampling across Queensland, Australia. Measures included drug use, drug-driving behavior and self-regulation. Results: A hierarchical binary logistic regression showed that, aside from problematic drug use predicting drug-driving, higher scores for age, effort/importance, an indicator of internalization of regulatory processes, and trait self-regulation significantly predicted a decrease in the likelihood of young adult drug-driving, with 61% variance accounted for in the model. Conclusions: Problematic drug use as the underlying issue contributing to drug-driving requires continued attention. However, viewing the issue of drug-driving as the result of unmet inherent psychological needs supports the notion that meeting these needs may reduce drug-driving in the long-term, instead of relying on the short-term effectiveness of enforcement measures. The study contributes to the limited research understanding the role of self-regulation in drug-driving behaviors. The implications of these findings include recommendations for psychological-based interventions guided by self-determination theory targeting young adults' drug-driving and more generally their long-term safe driving practices.